Voorwaardelikheid in studentetekste : ŉ Korpusgebaseerde analise - Meintjes, Zanétte (Stellenbosch Papers in Linguistics Plus, 2024)
During university studies, students are expected to primarily communicate with the academic discourse community by means of written texts. Although students must be able to produce various academic texts for this communication, the most common text that each student should have the skill to write is the academic argument. Such an argument consists of a specific structure, and is largely determined by creating coherence between the various components that make up this structure. Therefore, students must have the ability to guide the reader through the argument in an explicit manner. This accompaniment takes place, among other things, by using words and phrases that fulfil a conjunctive function. Conditionality is used to express the hypothetical or potential nature of certain matters. Words and phrases that have the function of conditionality are therefore non-factual in nature since the author intends to create a link between a specific situation and their opinion on the desirability or undesirability of that situation on an explicit manner to the reader. Although the way in which conditionality in languages ​​other than Afrikaans has been evaluated in student texts, the main objective of this article is to specifically evaluate its usage in the written argumentative texts of Afrikaans-speaking first-year students. The aim is to gain a better understanding of the type of conditionality words and phrases used, their occurrence and use, as well as determining how this use contributes to the overall coherence of these arguments. In addition, the aim is also to identify any other shortcomings in the use of conditionality, and to make specific recommendations regarding skill development in this regard.